Analisis Profil Laboratorium Biologi di SMA Negeri 1 Pemangkat Kabupaten Sambas Sesuai Standar Kementerian Pendidikan dan Kebudayaan RI - Luthfi, Nanda; Candramila, Wolly; Yuniarti, Anisyah (UNIB Press, 2026)
Biology learning emphasizes analytical, inductive, and deductive thinking to address problems related to the surrounding environment. Effective biology education is influenced by various factors, including students, educators, learning environments, and the availability of laboratory facilities. Well-equipped and professionally managed laboratories play a crucial role in supporting hands-on science learning. However, disparities in laboratory equipment availability across schools potentially lead to unequal learning outcomes. This study aimed to describe the profile of the biology laboratory at SMA Negeri 1 Pemangkat. The research was conducted from November to December 2024 using a survey method with a quantitative descriptive approach. The research sample consisted of the head of the biology laboratory. The findings show that all aspects of the laboratory room met the standards of Permendikbud No. 8 of 2018. However, several components related to the storage of laboratory tools and materials did not meet the required standards. These included unlocked material storage cabinets, insufficient equipment storage capacity, and unlabeled tools. Overall, the laboratory facilities and infrastructure scored between 69% and 100%, while laboratory management aspects ranged from 29% to 100%. These results highlight the need for improved storage management to ensure better laboratory functionality and support biology learning.